Energy sources : fundamentals of chemical conversion processes and applications - Viswanathan, B. (Balasubramanian) (Elsevier, 2016)
Energy Sources: Fundamentals of Chemical Conversion Processes and Applications provides the latest information on energy and the environment, the two main concerns of any progressive society that hopes to be sustainable in the future. Continuous efforts have to be exercised in both these areas by any of the developing communities, as concern over energy conversion continues to evolve due to various ecological imbalances, including climate change. This book provides the fundamentals behind all energy conversion processes, identifies future research needs, and discusses the potential application of each process in a clear-and-concise manner. It is a valuable source for both chemists and chemical engineers who are working to improve current and developing future energy sources, and is a single reference that deals with almost all energy sources for these purposes, reviewing the fundamentals, comparing the various processes, and suggesting future research directions.